Taxing mobile and overconfident top earners - Haufler, Andreas,Nishimura, Yukihiro (Collaborative Research Center Transregio 190, 2022)
We set up a simple model of tax competition for mobile, highly-skilled and overconfident managers. Firms endogenously choose the compensation scheme for managers, which consists of a fixed wage and a bonus payment in the high state. Managers are overconfident about the probability of the high state and hence of receiving the bonus, whereas firms and governments are not. When governments maximize tax revenues, we show that overconfidence unambiguously reduces the bonus tax rate that governments set in the non-cooperative tax equilibrium, while increasing tax revenues. When the government objective incorporates the welfare of resident managers, however, bonus taxes also serve a corrective role and may rise in equilibrium when overconfidence is increased.
10419/256785
Keywords: Graue Literatur; Overconfidence; bonus taxes; tax competition; migration